Evaluasi Sistem Perpipaan Distribusi Air Bersih PDAM Tirtamalem Unit Kabanjahe Berbasis Simulasi EPANET 2.0 - Rahayu, Silda Adi; Indrawan, Ivan; Sitepu, Yudithia Banta Karunia; Zafira, Nesa; Kurniati, Roselyn Indah (Jurnal Riksa Cendikia Nusantara, 2026)
PDAM Tirta Malem was established to fulfill the community’s clean water needs in Kabanjahe District through the provision of high-quality and sustainable water distribution services. The water source utilized to meet the water demand in Kabanjahe District is the Lau Bengap Spring, which has a production discharge of 50 liters/second. The problems occurring within the distribution piping system include the significant elevation difference between the reservoir and the service area, as well as the pipeline network passing through community plantations, which may lead to pipe leakage.This study aims to evaluate the clean water distribution piping system of PDAM Tirta Malem, Kabanjahe Unit, using the EPANET 2.0 software. The results indicate that the system experiences water losses of 37% and negative pressure in the pipelines reaching up to −4.16 m, causing water to be inadequately distributed to the community. To overcome these problems, the installation of a booster pump with a head of 60 m is required. In addition, replacing the 200 mm diameter distribution pipe with a 250 mm diameter pipe can also be considered as an alternative solution.